An introduction to the concept and features of post- post modernism - Mohsen farmahini farahani,; Hassan manouchehri,; fallah, Amirhossein soltani; Mohammadhassan tajdari,; Sina janalizadeh, (International Journal of Psychosocial Rehabilitation, 2020)
The goal of the present paper is the introduction of post- post modernism and its essential features. In this line, with a descriptive- analytic approach, the present research aims at specifying the concept of post-post modernism and similar notions and depicting the features of post-post modernism addressing the roots of the formation of post-post modernism. Along with criticizing modernism and post-modernism, the post- post modernism also approves of some of the perspectives of them each. The philosophical perspectives of post- post modernism contain some elements of both the modernism and post-modernism currents. This movement has also been established under various names such as trans modernism, semi- modernism, new modernism, meta-modernism, and digital modernism. Two major features of post-post modernism can be mentioned to be access and abundance or excess. Post-post modernism criticizes pessimism, absurdity, relativism and anti-enlightenment while approving optimism, absolutism, foundationalism and universalism to a logical extent and put the relieving of meta-narrations as its agenda. Besides this, it places a great emphasis on universality and the spread of the importance of various cultures. This is while post-modernism is more focused on DE and hence it talks about deconstruction. In post-post modernism, the focus is on RE and hence, it talks about regeneration. The emphasis of post-post modernism on code, game, Google, access, super text, multi-narrative, and contrasting combination creates specific training implications where there is the need to attempt in this regard.